Isotopic labelling applied to the infrared spectra of metal complexes - Engelter, Carola (Department of Chemistry, 2016)
The infrared spectra of pyridine adducts of first transition series metal(II) acetylacetonates are discussed in relation to the band shifts induced by ¹⁵N-labelling and deuteration of the pyridine ring and by metal ion substitution. ¹⁵N-Labelling aids in establishing the pyridine ring vibrations, while deuteration and metal substitution are more useful in assigning the νM-L frequencies. Results of the isotopic labelling study lead to a revision of previously-reported νM-O and vC---O frequencies. This technique also facilitates assignment of the νM-N vibrations, observed in the region below 200 cm⁻¹. The occurrence of these bands in this spectral region was expected because of the known relative weakness of the M-N bond strength in pyridine adducts. The effects on the spectra resulting from introduction of a variety of substituents into the pyridine ring are discussed on the basis of the electronic effects of the substituents. After allowing for mass effects, electron-withdrawing substituents are found to decrease νNi-N frequencies while electron-releasing substituents exert negligible effect on the νNi-N bands. An opposite trend is, however, observed for the νNi-O bands and is explained. An investigation of a series of aniline and p-toluidine complexes of first transition metal(II) isothiocyanates is reported.